2021
DOI: 10.1177/2325967121s00274
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play in Adolescent Baseball Players after SLAP Repair (131)

Abstract: Objectives: Superior labrum from anterior to posterior (SLAP) tears are increasingly common shoulder injuries in adolescent athletes who participate in repetitive overhead throwing. The purpose of this study is to evaluate adolescent baseball athletes who undergo SLAP repair in order to determine their long-term progression of play, surgical outcomes, and overall satisfaction with surgery. Methods: Patients between the ages of 10-19 who underwent a SLAP repair over a 10-year period from 2008-2018 with minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Overall, there was a 76.3% rate of RTS at any level, and of the 1212 patients who reported the degree to which they returned, 305 (25.2%) were unable to perform at their prior level.The rate of RTS within a specific surgical procedure was reported in 16 studies # (n = 1532 patients) and was 76.3%, 67.9%, and 73.6% after arthroscopic labral repair, open labral repair, and Latarjet, respectively. Four studies 13 , 33 , 45 , 53 reported surgical characteristics with only cumulative cohort RTS rates and were subsequently excluded from this surgery-specific RTS subgroup analysis ( Table 3 ). Proportion weighed meta-analysis demonstrated an overall RTS rate of 73% and a 40.7% rate of return to prior level among the studies that assessed psychological factors associated with RTS ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, there was a 76.3% rate of RTS at any level, and of the 1212 patients who reported the degree to which they returned, 305 (25.2%) were unable to perform at their prior level.The rate of RTS within a specific surgical procedure was reported in 16 studies # (n = 1532 patients) and was 76.3%, 67.9%, and 73.6% after arthroscopic labral repair, open labral repair, and Latarjet, respectively. Four studies 13 , 33 , 45 , 53 reported surgical characteristics with only cumulative cohort RTS rates and were subsequently excluded from this surgery-specific RTS subgroup analysis ( Table 3 ). Proportion weighed meta-analysis demonstrated an overall RTS rate of 73% and a 40.7% rate of return to prior level among the studies that assessed psychological factors associated with RTS ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…between 70% and 95%. [31][32][33][34][35][36][37][38][39][40][41][42][43] However, the estimates of the rate of return to preinjury levels of activity and competition are currently limited, potentially due to a lack of activity-level assessment standardization. 22,30,37 A recent meta-analysis identifying studies reporting RTS after surgery for shoulder instability found that, on average, 73% of people returned to any sport and 65% returned to their preinjury level of sport.…”
mentioning
confidence: 99%
See 3 more Smart Citations